2016
DOI: 10.1179/1743294415y.0000000049
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterisation, hardness and antibacterial properties of Zn–Ni–TiO2 nanocomposites coatings

Abstract: Zn-Ni-TiO 2 nanocomposites with various amounts of TiO 2 were successfully prepared by electroplating method on copper substrates using an acidic solution with TiO nanoparticles in 2 suspension. The composition and morphology of the composite coatings were characterised respectively using of scanning electron microscope (SEM), energy dispersive spectrometer and elemental mapping analysis system. The microhardness of the nanocomposite coatings was investigated. The antibacterial activity of Zn-Ni-TiO 2 nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Second, silver ions can produce reactive oxygen species (ROS) by catalyzing molecule oxygen in water, and ROS will cause bacteria death . The bactericidal mechanisms of Ag‐bioactive glass films can still work in vivo, which is unlike the photocatalysis related bactericidal mechanism of TiO 2 films …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, silver ions can produce reactive oxygen species (ROS) by catalyzing molecule oxygen in water, and ROS will cause bacteria death . The bactericidal mechanisms of Ag‐bioactive glass films can still work in vivo, which is unlike the photocatalysis related bactericidal mechanism of TiO 2 films …”
Section: Resultsmentioning
confidence: 99%
“…30 The bactericidal mechanisms of Ag-bioactive glass films can still work in vivo, which is unlike the photocatalysis related bactericidal mechanism of TiO 2 films. [24][25][26]31 Together with copper, silver is another effective inorganic antimicrobial regent. The studies have showed that Ag + ions have lower minimum inhibitory concentrations against bacteria including S. aureus and E. coli (MIC, 0.03-8 vs 256-448 lg/mL) and smaller Lethal doses 50 for L929 mouse fibroblast cells (LD50, 3.5910 À3 vs 2.3910 À1 mmol/L) than Cu 2+ ions.…”
Section: Antibacterial and Bioactivity Testsmentioning
confidence: 99%
“…To prevent agglomeration, various methods can be used such as organic additives, agitation of the solution, current density, etc. Treatment of the nanoparticles prior to deposition is varied throughout the field but the most common methods used for particle suspension are magnetic stirring, sonication or a combination of stirring and sonication prior to and during deposition [11][12][13]. In addition to treatment of the nanoparticles, concentration in the bath also affects the quality of the coatings.…”
Section: Dispersion Of Particlesmentioning
confidence: 99%
“…Metal matrix composite (MMC) coatings are promising materials developed by inclusion of a dispersed reinforcing material into a metal matrix. MMC's can replace traditional materials through their ability to offer improved mechanical and physical properties such as increased hardness, wear resistance, low thermal expansion coefficients, lubrication properties, antibacterial properties and improved corrosion resistance [1][2][3][4][5][6][7][8][9][10][11]. Nanosized particle incorporation 2 A/dm 2 , 23 ± 2°C Ultrasonication and solution stirring during deposition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation